Creating reflexivity in low attaining year 11 pupils in the catholic religious education classroom - Ossei-Brainoo, J (2020)
In this dissertation I explored the intention of having reflexivity as a learning process in the RE classroom, especially in the Catholic RE classroom. It can be argued to be more effective in an acknowledged confessional indoctrinate setting, where the RE classroom is a space pupils can critically interpret various traditions in the quest of finding their voice and understanding others. The confessional setting acts as the experiential starting point of the critical interpretation happening in the RE classroom. More importantly, the catechism of the Catholic Church arguably makes reflexivity more susceptible to RE in a Catholic School. An element of religious literacy can be seen as paramount in reflexivity as a learning process. Although the lockdown and a few other limitations meant I was not able to complete my practitioner research which focused on using mixed methods, the interviews held focused on discussing the research questions: